2003
DOI: 10.1029/2000jc000379
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric teleconnections involving the Southern Ocean

Abstract: [1] I review the characteristic patterns of low-frequency (interannual and subdecadal) variation in atmospheric circulation over the Southern Hemisphere (SH) extratropics and their climatic associations (e.g., temperature, precipitation, winds, sea surface temperatures (SSTs), and sea ice conditions) for the Southern Ocean. The considerable spatial and temporal limitations of the observational database have strongly conditioned the pace of our understanding of SH teleconnections, particularly for the Pacific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 178 publications
(370 reference statements)
9
92
0
1
Order By: Relevance
“…For example, Lefebvre et al (2004) showed that the SAM has a pronounced nonannular component that generates low (high) pressure anomalies to the west of the Antarctic Peninsula during strongly positive (negative) SAM events, thereby mapping onto the ASL. Similarly, several authors (e.g., Carleton 2003;Yuan and Li 2008) demonstrated that tropical Pacific forcing associated with ENSO is rapidly transmitted to the southeast Pacific via the PSA standing wave train and modulates the intensity and geometry of the ASL. Fogt et al (2011) emphasized the role of the interaction between the SAM and ENSO in shaping the response of the ASL to large-scale climate variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lefebvre et al (2004) showed that the SAM has a pronounced nonannular component that generates low (high) pressure anomalies to the west of the Antarctic Peninsula during strongly positive (negative) SAM events, thereby mapping onto the ASL. Similarly, several authors (e.g., Carleton 2003;Yuan and Li 2008) demonstrated that tropical Pacific forcing associated with ENSO is rapidly transmitted to the southeast Pacific via the PSA standing wave train and modulates the intensity and geometry of the ASL. Fogt et al (2011) emphasized the role of the interaction between the SAM and ENSO in shaping the response of the ASL to large-scale climate variability.…”
Section: Discussionmentioning
confidence: 99%
“…The ASL has been suggested both to experience significant modulation by the major atmospheric modes (Chen et al 1996;Simmonds and King 2004) and to have intensified in recent decades (Turner et al 2009). It has been suggested that the Pacific-South America (PSA) teleconnection, which plays a prominent role in transmitting ENSO events to high southern latitudes (Carleton 2003), may be significant in modulating the ASL. (The PSA is a standing wave train of atmospheric anomalies that originates in the western equatorial Pacific and manifests in a series of high and low pressure systems crossing southeastward across the South Pacific toward the southwest AtlanticWeddell Sea.)…”
Section: Driving Mechanisms Of the Observed Variabilitymentioning
confidence: 99%
“…Simmonds & Jacka 1995, Yuan & Martinson 2001, Carleton 2003, and this may impact on the sea-ice/rainfall relationship. However, it should be noted that the set of anomalously wet and dry years derived from Fig.…”
Section: Potential Relationships With Ensomentioning
confidence: 99%
“…However, they found that statistically analysis using climatological data within large area explained partially long-term and short-term variations. In addition, previous researches (Jenouvrier et al, 2004;White et al, 2002;, Carleton, 2003;Yuan, 2004;Lee et al, 2010) suggested that these short-and long-term changes in sea water temperature in the Southern Ocean was linked to ENSO events, and these change in sea water temperature matched well with the sea-ice extent and the propagation of the Antarctic Circumpolar Wave (ACW). In particular, the ACW and ENSO cycles are considered as main factors driving the warming trend around the Southern Ocean (Karoly et al, 1989;Rasmusson and MO, 1993;, and the ACW which propagates eastward with the circumpolar flow with a period of 4-5 years also has been linked to the ENSO cycles.…”
Section: Resultsmentioning
confidence: 96%